Pedagogical intervention: a work aimed at quality in the teaching-learning process (Research, Society and Development, 2020)
This article aims to present the result of an exploratory research of the descriptive and qualitative type, which emerges from the result of the Diagnostic Assessment developed in a public school in Mato Grosso, which leads the State Department of Education and Culture-SEDUC-MT to establish a policy with the intention of reversing the situation. To this end, the Pedagogical Intervention-PIP Project is created. The project was developed in all classes by the professors, both in the Elementary School of the Early Years, as well as in the Final Years. After completing the PIP, it was possible to verify that the pedagogical activity being planned, organized, even considering the content provided for the class, as well as its peculiarities inherent to the learning process, the teacher had the device to also be able to review the teaching act (Anastasiou, 2014). In this context, it is evident that the act of evaluating is always necessary (Vilas Boas, 2008), as it provides us with elements and or results that point to both improvement and permanence. This, especially when it comes to the school, becomes an extremely important device in order to seek better results in the process of teaching and learning. The work still shows evidence that teacher training may be an indispensable resource to enable improvements in the teaching-learning process.